2018
DOI: 10.1086/697253
|View full text |Cite
|
Sign up to set email alerts
|

The Parties in Our Heads: Misperceptions about Party Composition and Their Consequences

Abstract: We document a large and consequential bias in how Americans perceive the major political parties: people considerably overestimate the share of party-stereotypical groups in the parties. For instance, people think that 32% of Democrats are LGBT (6% in reality) and 38% of Republicans earn over $250,000 per year (2%). Experimental data demonstrate that these misperceptions are genuine and party-speci c, not artifacts of expressive responding, innumeracy, or ignorance of base rates. These misperceptions are widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
237
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(298 citation statements)
references
References 56 publications
17
237
4
Order By: Relevance
“…By highlighting an overarching identity, politicians, the media and opinion leaders could help reduce political division around the issue. Second, a growing body of work shows that misperceptions of the other side underlie polarization 96,97 . Therefore, it is likely important to combat misinformation that could generate partisan motivated reasoning and inaccurate beliefs (see "Fake news and misinformation" below).…”
Section: Culturementioning
confidence: 99%
“…By highlighting an overarching identity, politicians, the media and opinion leaders could help reduce political division around the issue. Second, a growing body of work shows that misperceptions of the other side underlie polarization 96,97 . Therefore, it is likely important to combat misinformation that could generate partisan motivated reasoning and inaccurate beliefs (see "Fake news and misinformation" below).…”
Section: Culturementioning
confidence: 99%
“…Further, Ahler and Sood () found that this subjective understanding has the potential to increase partisanship and polarization and that correcting any inflated sense of alignment can work to reduce this partisan bias.…”
Section: Traditional Identity Politicsmentioning
confidence: 99%
“…This makes for a unidimensional or monolithic distinction between the good people and the bad people (in religion, in status, in culture, and in politics), and it is a danger to a pluralistically organized democracy. (p. 86) Further, Ahler and Sood (2017) found that this subjective understanding has the potential to increase partisanship and polarization and that correcting any inflated sense of alignment can work to reduce this partisan bias.…”
Section: Objective and Subjective Social Sortingmentioning
confidence: 99%
“…Racial and partisan identities have become more closely associated since the 1970s (Carmines and Stimson, 1989;Green, Palmquist, and Schickler, 2002;Tesler, 2016;Kuziemko and Washington, 2018). Perceptually, Ahler and Sood (2018) show that African Americans are regarded as prototypical Democrats, so much so that the public dramatically overestimates the share of the Democratic party that is black. Whites are strongly associated with the Republi-…”
Section: Race and Partisanshipmentioning
confidence: 99%